Situation Report: Hungary, 6 February 1973 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. CSO Report on Fulfillment of 1972 Economic Plan Car Import Program for 1973 Nationwide Workers' Guard Meetings University Admission System Changed Licenses, Patents, and Know-How: Some Specific Examples of Hungary's Trade in These Products Agricultural Production Targets for 1973 Machinery to Mechanize Tobacco Production Imported from the West